2016
DOI: 10.1002/yea.3146
|View full text |Cite
|
Sign up to set email alerts
|

Screening for new brewing yeasts in the non‐Saccharomyces sector with Torulaspora delbrueckii as model

Abstract: This study describes a screening system for future brewing yeasts focusing on nonSaccharomyces yeasts. The aim was to find new yeast strains that can ferment beer wort into a respectable beer. Ten Torulaspora delbrueckii strains were put through the screening system, which included sugar utilization tests, hop resistance tests, ethanol resistance tests, polymerase chain reaction fingerprinting, propagation tests, amino acid catabolism and anabolism, phenolic off-flavour tests and trial fermentations. Trial fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
1
27

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 51 publications
(63 reference statements)
4
108
1
27
Order By: Relevance
“…Furthermore, the finished beers were characterized by a low real attenuation (37%) and, consequently, low ethanol concentration (2.66% v/v), indicating that T. delbrueckii could be used also to produce low-alcohol beers. Similar results were found by Michel et al [39], which tested 10 T. delbrueckii strains from different habitats and found that two strains can be suitable for producing low-alcohol beer, owing to their inability to ferment maltose and maltotriose, but still produced good flavor. However, these authors found also one strain able to ferment the beer wort to an ethanol concentration of 4% v/v with a desirable fruity and floral aroma, in consequence of production of high amounts of 2-phenylethanol (23.7 mg/L) and amyl alcohols (64.83 mg/L).…”
Section: Non-conventional Yeasts For Bioflavoringsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the finished beers were characterized by a low real attenuation (37%) and, consequently, low ethanol concentration (2.66% v/v), indicating that T. delbrueckii could be used also to produce low-alcohol beers. Similar results were found by Michel et al [39], which tested 10 T. delbrueckii strains from different habitats and found that two strains can be suitable for producing low-alcohol beer, owing to their inability to ferment maltose and maltotriose, but still produced good flavor. However, these authors found also one strain able to ferment the beer wort to an ethanol concentration of 4% v/v with a desirable fruity and floral aroma, in consequence of production of high amounts of 2-phenylethanol (23.7 mg/L) and amyl alcohols (64.83 mg/L).…”
Section: Non-conventional Yeasts For Bioflavoringsupporting
confidence: 87%
“…All these results might indicate that the fermentation performance of T. delbrueckii strongly depends on the strain. The overall speed of fermentation seems to be slower than that of usual S. cerevisiae brewing strains; however, this species ferments both high and medium original gravity worts, with a high production of higher alcohols and esters [37,39]. The ethanol content of final beers varied from 0.8 to 4% (v/v), as some strains will not ferment all wort sugars [38,39].…”
Section: Non-conventional Yeasts For Bioflavoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of new fermentation technologies for optimizing beer quality and producing beers with particular flavor profiles is one of the worldwide trends in brewing [11,12,14]. In this context, there is a growing demand for new and improved sorghum beer yeast strains to obtain beers with constant organoleptic characteristics.…”
Section: Volatile Compounds Of the Beersmentioning
confidence: 99%
“…In recent years, growth of non-Saccharomyces yeasts has been observed also in fermentation inoculated with S. cerevisiae, suggesting a greater contribution of these yeasts to the flavour and quality of alcoholic beverages than previously thought. Thus, the use of Torulaspora delbrueckii was evaluated for beer production in both pure and mixed cultures with Saccharomyces cerevisiae [11,12]. Other examples of non-Saccharomyces yeasts include Brettanomyces, which is used in atypical spontaneously fermented Belgian beer or "lambic beer" [13] and Candida zemplinina in craft beer fermentation [14].…”
Section: Introductionmentioning
confidence: 99%